Los musulmanes y Jerusalén - Abu-Amr, Ziad (Revista de Estudios Árabes, 2014)
Professor Abu-Amr says that Muslims recognize the importance of Jerusalem to Christians and Jews, but stresses that its Muslim religious prominence and character entitles them to it. Israeli attempts to judaize the city is totally rejected by Palestinian and Muslims the world over. Furthermore, nationalist Palestinians consider it the capital of Palestine. In view of previous failed attempts by Jewish extremists to destroy the al-Aqsa Mosque, many Muslims fear that if the occupation continues, they may eventually succeed. He considers that there will be no permanent solution to the conflict without the total restitution of the city to its rightful owners.